KEBIJAKAN PENGEMBANGAN KOLEKSI DI PERPUSTAKAAN AKADEMIK NEGARA BAGIAN IMO NIGERIA DAN TANZANIA - Savitri, Agustin Gita; Zulaikha, Sri Rohyanti (Fihris: Jurnal Ilmu Perpustakaan dan Informasi, 2023)
Libraries play a strategic role in improving the quality of education by providing informative and relevant collections. Collection development policies are essential, particularly for academic libraries that support theses and research conducted by the academic community. This study employs a literature review method, referencing various sources such as scientific books, journal articles, research reports, and regulations in both printed and electronic formats. Additionally, the study compares two journal articles discussing collection development policies in academic libraries in Africa, namely the Imo State Academic Library and the Tanzanian Academic Library. The findings indicate that both libraries have implemented collection development policies, including selection, acquisition, user studies, preservation, weeding, evaluation, and collaboration. However, the involvement of users in the selection process of library materials remains limited. Therefore, this study recommends increased user involvement in the selection process, the establishment of a Collection Development Department, periodic weeding, and enhanced collaboration among libraries.